2023
DOI: 10.1007/s10661-022-10887-y
|View full text |Cite
|
Sign up to set email alerts
|

Do biodiversity monitoring citizen science surveys meet the core principles of open science practices?

Abstract: Citizen science (CS), as an enabler of open science (OS) practices, is a low-cost and accessible method for data collection in biodiversity monitoring, which can empower and educate the public both on scientific research priorities and on environmental change. Where OS increases research transparency and scientific democratisation; if properly implemented, CS should do the same. Here, we present the findings of a systematic review exploring “openness” of CS in biodiversity monitoring. CS projects were scored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…While these inventories with detailed morphological, genetic and ethnobotanical details offer a solid register, they often lack temporal occurrence data per landrace. To increase the number of observations in space and time, citizen science and crowdsourcing approaches hold great promise to underpin long-term diversity monitoring (Johnston et al, 2022;Suter et al, 2023). An example of such a pilot-level effort is the WikiPapa Platform (www.wikipapa.org).…”
Section: Discussionmentioning
confidence: 99%
“…While these inventories with detailed morphological, genetic and ethnobotanical details offer a solid register, they often lack temporal occurrence data per landrace. To increase the number of observations in space and time, citizen science and crowdsourcing approaches hold great promise to underpin long-term diversity monitoring (Johnston et al, 2022;Suter et al, 2023). An example of such a pilot-level effort is the WikiPapa Platform (www.wikipapa.org).…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, a set of guiding principles were instantiated with the aim to establish a standard for scientific data, ensuring that it is FAIR: Findable, Accessible, Interoperable and Reusable (Wilkinson et al., 2016). Nevertheless, it has been shown that despite the development of tools to facilitate open science, abounding toolkits and data and code repositories, the potential of citizen science to be practiced as open science is not always realised by those responsible for the projects, with missing information in published outcomes having a significant impact on the openness of the research projects that were analysed (Suter et al., 2023) and low uptake of complex data management plan tools (Roman et al., 2021). However, CS projects such as StreetSpectra provide an exemplary testbed for the usability of open science infrastructure and for testing how FAIR research is.…”
Section: Science Innovation Through Citizen Sciencementioning
confidence: 99%
“…Not all CS datasets are open, and in some cases this would be undesirable because of safety or privacy concerns, but when they are open, they can be used by other researchers or decision-makers, on their own or in combination with other datasets, to contribute to the medium-and long-term outcomes described under pathways 1 and 2. Open datasets (and publications) can also, in the long term, democratise science as they can be viewed by and interrogated by anyone, potentially increasing accountability, transparency, and trust, as well as widening involvement in the scientific and knowledge-creation processes (Suter, Barrett, and Welden 2023).…”
Section: Implications Of Lack Of Diversity For Pathwaymentioning
confidence: 99%